Gravitational lensing of quasi-stellar objects by their damped Lyα absorbers - Bartelmann, Matthias; Leyb, Avraham (Arxiv, 1995)
Damped Lyman-alpha absorbers are believed to be associated with galactic disks. We show that gravitational lensing can therefore affect the statistics of these systems. First, the magnification bias due to lensing raises faint QSOs above a given magnitude threshold and thereby enhances the probability for observing damped absorption systems. Second, the bending of light rays from the source effectively limits the minimum impact parameter of the line-of-sight relative to the center of the absorber, thus providing an upper cut-off to the observed neutral hydrogen (HI) column density. The combination of these effects yields a pronounced peak in the observed abundance of absorbers with high column densities (>2*10^{21} cm^{-2}) and low redshifts (z<1). The inferred value of the cosmological density parameter of neutral hydrogen, Omega_{HI}, increases with increasing redshift and luminosity of the sources even if the true HI density remains constant. This trend resembles the observed evolution of Omega_{HI}(z). Damped Lyman-alpha absorbers with column densities >10^{21} cm^{-2} and redshifts 0.5<z<1 are reliable flags for lensed QSOs with a close pair of images separated by 0.3 arcsec. Detection of these gravitational lensing signatures with the Hubble Space Telescope can be used to constrain the depth of the absorber potential-wells and the cosmological constant.
Gesehen am 29.09.2017